Enhanced Carbon Dioxide Electroreduction to Carbon Monoxide over Defect‐Rich Plasma‐Activated Silver Catalysts. Issue 38 (10th August 2017) - Mistry, Hemma; Choi, Yong‐Wook; Bagger, Alexander; Scholten, Fabian; Bonifacio, Cecile S.; Sinev, Ilya; Divins, Nuria J.; Zegkinoglou, Ioannis; Jeon, Hyo Sang; Kisslinger, Kim; Stach, Eric A.; Yang, Judith C.; et al.
Abstract: Efficient, stable catalysts with high selectivity for a single product are essential if electroreduction of CO2 is to become a viable route to the synthesis of industrial feedstocks and fuels. A plasma oxidation pre‐treatment of silver foil enhances the number of low‐coordinated catalytically active sites, which dramatically lowers the overpotential and increases the activity of CO2 electroreduction to CO. At −0.6 V versus RHE more than 90 % Faradaic efficiency towards CO was achieved on a pre‐oxidized silver foil. While transmission electron microscopy (TEM) and operando X‐ray absorption spectroscopy showed that oxygen species can survive in the bulk of the catalyst during the reaction, quasi in situ X‐ray photoelectron spectroscopy showed that the surface is metallic under reaction conditions. DFT calculations reveal that the defect‐rich surface of the plasma‐oxidized silver foils in the presence of local electric fields drastically decrease the overpotential of CO2 electroreduction. Abstract : Plasma activation : Silver catalysts activated with an oxygen plasma treatment show extraordinary improvement for CO2 electroreduction compared to flat silver surfaces. Electric field effects on the defect‐rich plasma‐treated surface promote reduction of CO2 to CO at low overpotentials.